(untitled) (Bangladesh Journal of Plant Taxonomy, 2021)
Recognition of species is essential in a variety of domains, most remarkably biology, biogeography, ecology, as well as conservation. The genus Stellaria L. (Caryophyllaceae) has over 120 species spread across Europe and Asia’s temperate zones. According to the most remarkable current treatments, nine species recognize Stellaria in Iran. These species are categorized into two types. Despite the broad distribution of several Stellaria species in Iran, no research on their genetic variability, method of divergence, or dispersion trends is accessible. As a result, we conducted genetic and morphological research on six Stellaria species and two of their closest relatives gathered from various habitats in Iran. This research aims to 1) Can SCoT markers be utilized to recognize Stellaria species? 2) What are the genetic characteristics of the mentioned taxa in Iran? and 3) To examine the interrelation of the species. In this research, ten SCoT markers were employed for molecular analysis, and 112 accessions were utilized for morphological study. The genetic distances were calculated using the Jaccard similarity coefficient, and descriptive data on the populations were used to estimate genetic parameters. There were 98 polymorphic bands all over. The integration of morphological and SCoT data demonstrated that the Stellaria species of Iran could be delimited and recognized. The Stellaria species are genetically unique; however, they share some similar alleles, according to AMOVA and STRUCTURE analyses. Bangladesh J. Plant Taxon. 28(2): 317-328, 2021 (December)